2021
DOI: 10.21203/rs.3.rs-303246/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Prediction of Groundwater Potentiality Mapping Using Machine Learning Algorithms

Abstract: Machine learning techniques offer powerful tools for the assessment and management of groundwater resources. Here, we evaluated the groundwater potential maps (GWPMs) in Md. Bazar Block of Birbhum District, India using four GIS-based machine-learning algorithms (MLA) such as predictive neural network (PNN), decision tree (DT), Naïve Bayes classifier (NBC), and random forest (RF). We used a database of 85 dug wells and one piezometer location identified using extensive field study, and employed 12 influencing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Kulisz et al [24] tested the capacity of ANN methods to model the water quality index in groundwater and found satisfactory accuracy. Saha et al [25] evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment. They evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kulisz et al [24] tested the capacity of ANN methods to model the water quality index in groundwater and found satisfactory accuracy. Saha et al [25] evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment. They evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment [25].…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al [25] evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment. They evaluated groundwater potential maps (GWPMs) using machine learning algorithms (MLA) and achieved satisfactory results for groundwater potentiality assessment [25]. Kumar et al [26] modelled groundwater drought indices using machine learning techniques, specifically ANN and random forest (RF), and found that the RF model showed superior performance [26].…”
Section: Introductionmentioning
confidence: 99%